2011
DOI: 10.1186/1471-2148-11-364
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of intron gain and loss in Drosophila

Abstract: BackgroundIt is widely accepted that orthologous genes have lost or gained introns throughout evolution. However, the specific mechanisms that generate these changes have proved elusive. Introns are known to affect nearly every level of gene expression. Therefore, understanding their mechanism of evolution after their initial fixation in eukaryotes is pertinent to understanding the means by which organisms develop greater regulation and complexity.ResultsTo investigate possible mechanisms of intron gain and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(83 citation statements)
references
References 78 publications
8
74
1
Order By: Relevance
“…In mammals and Drosophila, intron losses have been found to occur preferentially in highly expressed genes. 6,9 Researchers have suggested that this supports a reverse transcriptase model of intron loss. 15 The reverse transcriptase model is an entirely different model that attempt to explain the pattern of intron loss at mutation level.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In mammals and Drosophila, intron losses have been found to occur preferentially in highly expressed genes. 6,9 Researchers have suggested that this supports a reverse transcriptase model of intron loss. 15 The reverse transcriptase model is an entirely different model that attempt to explain the pattern of intron loss at mutation level.…”
Section: Introductionmentioning
confidence: 89%
“…[1][2][3][4][5][6][7][8][9][10] However, it is not clear whether these intron losses occur by chance or are driven by selective forces. In principle, intron loss can be positively selected if the existence of that intron is deleterious to the host organism or if its detriments overwhelm its benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to the dipterans, Cnn is encoded by more exons in all species investigated here with a trend toward exon fusion in the dipterans. The most common mechanism for intron loss is mediated by reverse transcriptase (Coulombe-Huntington and Majewski 2007;Yenerall et al 2011), but our results suggest that cnn introns are lost by genomic deletions (Llopart et al 2002;Yenerall et al 2011). Our comparison of the exon structure of cnn orthologs shows a potential intermediate step in this process, especially within the hymenopterans.…”
mentioning
confidence: 85%
“…Protein alignments between all the species in this study suggest that the short sequences flanking fusion points are divergent between orders and continue to evolve rapidly after the fusion event within orders. Global analyses of Drosophila have shown that most introns are lost by a reverse transcriptase mechanism, resulting in the perfect excision of the intron (Coulombe-Huntington and Majewski 2007; Yenerall et al 2011). A rare second mechanism of intron loss in Drosophila is precise and imprecise genomic deletion by nonhomologous end joining (NHEJ) during DNA break repair (Llopart et al 2002;Yenerall et al 2011).…”
Section: A Potential Buffering Function For Mpos In Drosophila Cnnmentioning
confidence: 99%
See 1 more Smart Citation